STRATEGI NAFKAH RUMAH TANGGA PETANI KOPI DI DESA KENDENAN KECAMATAN BARAKA KABUPATEN ENREKANG - Rifki Aditya Saputra; Amruddin Amruddin; Nadir Nadir (Universitas Andi Djemma Palopo, 2022)
This study aims to determine the form of farmer household income strategies and household income capital in Kendena Village, Baraka District, Enrekang Regency in dealing with vulnerability. The research was carried out from November to December 2020 which was located in Kendenan Village, Baraka District, Enrekang Regency. Determination of informants is done by purposive sampling method or deliberately by taking 10%. The data collected in this study consisted of two types, namely primary data and secondary data. The results of the study show that the livelihood strategies used by farmers in Kendenan Village are of the same type of work and some are not the same type of work, and have different priorities. The classification of livelihood strategies in Kendenan Village includes 1.) Engineering of agricultural livelihoods is carried out by intensifying and extensifying agriculture. The strategy of expanding agricultural land (extensification) in Polo Slope Village is still possible for lowland rice farmers because the available land is still large. 2.) Double income pattern. The dual role of livelihood carried out by farming households, husband and wife each work in the same sector, husband and wife work but in different sectors, one member of the household has more than one type of work, each family member chooses another job , usually increase household income to survive. 3.) Spatial engineering is an effort carried out by mobilizing/moving residents both permanently and circularly (migration) in order to seek livelihood sources elsewhere. Farmers who migrate circularly in Kendenan Village, commute every day to earn a living outside the village so they can increase their income to meet their family's living needs.